Quercus rotundifolia Lam. Woodlands of the Southwestern Iberian Peninsula - Quinto-Canas, Ricardo (2022)
The holm oak woodlands as ecotonic phytocoenoses occur under different ecological conditions, and frequently representing the climax of edaphoxerophilous series of crests and siliceous rocky areas. In this paper we study the floristic, ecological, and biogeographical differences of the edaphoxerophilous holm oak woodlands of the southwestern Iberian Peninsula, included in the Querco rotundifoliae-Oleenion sylvestris suballiance. Our phytosociological (Braun–Blanquet methodol ogy) and numerical analysis (hierarchical cluster analysis) of three formerly described association and our own samples lead us to propose a new association: Ulici argentei-Quercetum rotundifoliae, growing mostly on semihyperoceanic Monchique Sierran Biogeographic District, on rocky slopes and outcrops derived from schists and greywackes. Moreover, we present an overview of ecological features and the diversity of plant communities occurring in the serial dynamic of the thermophile holm oak woodlands of the southwest of the Iberian Peninsula.